2011
DOI: 10.1002/pssb.201046583
|View full text |Cite
|
Sign up to set email alerts
|

Graphene allotropes

Abstract: Using the density-functional-based tight-binding method (DF-TB) we performed a systematic comparative study of stability, structural, and electronic properties for 12 various types of graphene allotropes, which are likely candidates for engineering of novel graphene-like materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

21
316
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 416 publications
(342 citation statements)
references
References 33 publications
21
316
1
4
Order By: Relevance
“…Previous DFT studies [20,[31][32][33][34][35] concerned with the calculation of electronic properties of graphynes classified them as semiconducting or metallic materials without investigating the possibility of the presence of Dirac cones. In one semiempirical study [36], which employed the density-functional-based tight-binding method, hints on the presence of a graphenelike electronic structure were given for one graphyne. We note in passing that Dirac cones were observed at interfaces of topological insulators [37,38].…”
mentioning
confidence: 99%
“…Previous DFT studies [20,[31][32][33][34][35] concerned with the calculation of electronic properties of graphynes classified them as semiconducting or metallic materials without investigating the possibility of the presence of Dirac cones. In one semiempirical study [36], which employed the density-functional-based tight-binding method, hints on the presence of a graphenelike electronic structure were given for one graphyne. We note in passing that Dirac cones were observed at interfaces of topological insulators [37,38].…”
mentioning
confidence: 99%
“…8,[12][13][14][15][16][17][18] Recently, it was shown that other two-dimensional materials can also be stable and that they widen the potential of two-dimensional materials for applications. [19][20][21][22] Of particular importance are graphene-like carbon allotropes, called graphyne structures composed of one-atom-thick sheets of carbon atoms but containing sp carbon bonds in addition to sp 2 hybridized bonds [23][24][25] (see Fig. 1).…”
mentioning
confidence: 99%
“…Two of these nets are enantiomorphic and only 11 Kepler nets are usually taken into consideration. There are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%